Reachability of Fractional Dynamical Systems with Distributed Delays in Control using $ψ$-Hilfer Pseudo-Fractional Derivative - Selvam, A. Panneer; Govindaraj, V. (Discontinuity, Nonlinearity, and Complexity, 2026)
This research investigates the reachability of linear and non-linear fractional dynamical systems with distributed delays in control using the $ψ$-Hilfer pseudo-fractional derivative in g-calculus. Grammian matrices, which are characterized by Mittag-Leffler functions, are used to provide necessary and sufficient criteria for reachability in the linear case, while Schauder's fixed point theorem is used to create sufficient conditions for reachability in the nonlinear case. A couple of numerical results is offered to explain the theoretical results.